Caracterização de criadores amadores e determinação de indicadores associados ao bem-estar de pássaros canoros criados em gaiolas - Paulo Eduardo Machado Goncalves (2013)
The aim of this study was to characterize the amateur bird breeders and determine indicators related to the well-being of wild songbirds. Questionnaires were applied from 2011 to 2013 to 109 owners of these birds in the state of Minas Gerais, Brazil. The questions were formulated, mostly dichotomously. It was also performed direct evaluations in the birds and the environments where they were raised. For the first time it was adopted a Reactivity Test in Domesticated Birds (RAS) based primarily on the reactivity of bird to human presence, as an adequate measure to be used as a well-being indicator index for wild birds. The first part of the study described the environment, the bird breeders, the bird itself and the management applied to the to the cage birds, evaluated from approximately 62 characteristics. The second part, performed by multivariate analysis from multiple correspondence did not provide a quantification, but an association measured by Euclidean approximation of the algebraic system, where the associated variables are in the same three-dimensional shape quadrant. It was observed a positive association between well-being and the number of people in the household, however a negative association in relation between well-being and the number of birds in the household (Inertia: 66 %). In the Multiple Correspondence Qualitative Analysis, the variable positive well-being was associated more closely to the owner who provides preventive drugs, that covers the cage at night, the rest state of the bird, and to the owner who provides a proper name to your bird, and secondly negative well-being was associated with restless animals and that is with the owner for a short period of time (chi-square: 38.42 %). It was conclude that singing is the key factor for the onset of human- bird interaction and that the longer the time of the bird with the same breeder, the greater the bonds of confidence achieved between them favoring the welfare of the bird and raising the bird breeding delightful to its owner.